Novel strains of Tomato Spotted Wilt Orthotospovirus (TSWV) are transmitted by western flower thrips in a context-specific manner - Senthilraja Chinnaiah; Arinder K. Arora; Kiran R. Gadhave (PLoS ONE, 2025)
Novel resistance breaking (RB) strains of tomato spotted wilt orthotospovirus (TSWV) capable of disrupting single gene resistance in tomato ( Sw- 5 b ) and pepper ( Tsw ) have been reported worldwide. Thrips, a supervector of TSWV, transmit these strains in a suite of specialty and staple food crops across the globe. However, transmission biology of RB strains remains virtually unexplored. We investigated various transmission parameters viz . inoculation efficiency, putative sex-specific differences in inoculation, virus accumulation, and source sink relationships to dissect these interactions. Six novel strains of TSWV, namely Tom-BL1, Tom-BL2, Tom-CA, Tom-MX, Pep-BL and Non-RB, transmitted by western flower thrips (WFT) were used and thrips were allowed four 24h consecutive inoculation accession periods (IAPs). Our results show that most strains were inoculated at all four IAPs, however, their rates differed across IAPs. Overall, WFT had highest inoculation efficiency at the first and lowest at the second IAP. Female thrips carried higher virus titers; however, males were better at inoculating TSWV. Furthermore, we did not find significant positive correlations in virus titers between the tissues used for TSWV acquisition, thrips and thrips-inoculated leaf discs. Males inoculated RB strains at 87% efficiency whereas Non-RB strain at 80% efficiency. Female thrips were 77% and 75% efficient at inoculating RB and Non-RB strains, respectively. This study furnishes new insights into the transmission biology of TSWV RB strains, especially from inoculation and thrips sex perspectives, and provides a baseline for future molecular studies surrounding ever evolving novel TSWV strains.